The impact of interindividual variation in NAT2 activity on benzidine urinary metabolites and urothelial DNA adducts in exposed workers. - Rothman, N (1996)
Several epidemiologic studies indicate that NAT2-related slow N-acetylation increases bladder cancer risk among workers exposed to aromatic amines, presumably because N-acetylation is important for the detoxification of these compounds. Previously, we showed that NAT2 polymorphisms did not influence bladder cancer risk among Chinese workers exposed exclusively to benzidine (BZ), suggesting that NAT2 N-acetylation is not a critical detoxifying pathway for this aromatic amine. To evaluate the biologic plausibility of this finding, we carried out a cross-sectional study of 33 workers exposed to BZ and 15 unexposed controls in Ahmedabad, India, to evaluate the presence of BZ-related DNA adducts in exfoliated urothelial cells, the excretion pattern of BZ metabolites, and the impact of NAT2 activity on these outcomes. Four DNA adducts were significantly elevated in exposed workers compared to controls; of these, the predominant adduct cochromatographed with a synthetic N-(3'- phosphodeoxyguanosin-8-yl)-N'-acetylbenzidine standard and was the only adduct that was significantly associated with total BZ urinary metabolites (r = 0.68, P < 0.0001). To our knowledge this is the first report to show that BZ forms DNA adducts in exfoliated urothelial cells of exposed humans and that the predominant adduct formed is N-acetylated, supporting the concept that monofunctional acetylation is an activation, rather than a detoxification, step for BZ. However, because almost all BZ-related metabolites measured in the urine of exposed workers were acetylated among slow, as well as rapid, acetylators (mean +/- SD 95 +/- 1.9% vs. 97 +/- 1.6%, respectively) and NAT2 activity did not affect the levels of any DNA adduct measured, it is unlikely that interindividual variation in NAT2 function is relevant for BZ-associated bladder carcinogenesis.